FOCUS GROUPS AND INTERVIEWS ANALYSIS: THE STATUS QUO AND PROSPECTS OF HONG KONG ECONOMY - Xu, Lin (PEOPLE: International Journal of Social Sciences, 2021)
Violent protests and COVID-19 have caused the downturn of Hong Kong’s economy. Under this circumstance, local youngsters are facing a colder job-hunting season. It aroused the author’s interest that in Hong Kong, a unique economy, how young people see their current life, the city’s state, and future. The point of this research lies in whether the young generation in Hong Kong is holding the same thoughts regarding the topics of the Hong Kong economy and what factors are influencing their thinking patterns. With Social Representations Theory, the analysis is conducted based on the answers from the chosen twelve local interviewees, aged between 23 and 30. The conclusions are: the interviewees’ attitudes toward different economic topics are influenced by their educational background, careers, gender, and living experience; what young people think may not be in line with or even go against the commonsense knowledge. These answers can be social representations of local youngsters in the sample regarding the Hong Kong economy at this stage. They can contribute to larger-scale surveys with local people and the application of Social Representations Theory in the future.